Contaminação por fungos antes e após limpeza e desinfecção de colchões hospitalares - Fernando, Francine da Silva e Lima de; Ferreira, Adriano Menis; Colombo, Tatiana Elias [UNESP]; Rubio, Fernando Gôngora; Almeida, Margarete Teresa Gottardo de (Universidade Federal de São Paulo (UNIFESP), Escola Paulista de Enfermagem, 2013)
OBJECTIVE: To verify the existence of fungal contamination prior to and following the cleaning and disinfection process of hospital mattresses used by patients with Candidemia. METHODS: Cross-sectional study analyzing 25 mattresses used by patients with Candidemia confirmed by blood culture from different hospital wards. The study made use of convenience samples. After growing the samples in an Agar Sabouraud Dextrose environment, isolated yeasts were identified by macroscopic, microscopic and physiologic characteristics. RESULTS: Analyses showed 15 (60%) mattresses contaminated by Candida spp. From these, 10 (66.7%) and five (33.3%) mattresses corresponded respectively to the collection prior to and following disinfection, with Candida parapsilosis being the isolated species with the highest frequency. CONCLUSION: Considering that half of the mattresses remained contaminated after cleaning and disinfection, there is a risk that these mattresses may act as potential secondary reservoirs in the infection chain.

OBJETIVO: Verificar se existe contaminação por fungos antes e após limpeza e desinfecção terminal de colchões hospitalares utilizados por portadores de candidemia. MÉTODOS: Estudo transversal que investigou 25 colchões de diferentes unidades hospitalares e utilizados por pacientes com candidemia, confirmados por hemocultura. Utilizou-se amostragem por conveniência. Após crescimento em Ágar Sabouraud Dextrose as leveduras isoladas foram identificadas pelas características macroscópicas, microscópicas e fisiológicas. RESULTADOS: Totalizou-se 15 (60%) colchões contaminados com Candida spp. Desse total, 10 (66,7%) e cinco (33,3%) corresponderam respectivamente à coleta antes e após a desinfecção dos colchões, sendo que a espécie mais frequentemente isolada foi Candida parapsilosis. CONCLUSÃO: Considerando que a metade dos colchões permaneceram contaminados após o processo de limpeza e desinfecção, pode-se inferir sobre o risco destes atuarem como reservatórios secundários na cadeia de infecção.
Fungal contamination of hospital mattresses before and following cleaning and disinfection
Keywords: Desinfecção; Auditoria de enfermagem; Enfermagem prática; Contaminação de equipamentos; Leitos; Candidemia; Fungos; Disinfection; Nursing audit; Nursing, practical; Equipment contamination; Beds; Candidemia; Fungi